Strategi Politik Perempuan Caleg Sumatera Barat dalam Pemilu 2014 - Putri, Indah Adi (Journal of Moral and Civic Education, 2017)
This paper focuses on the discussion of how the political strategy of women legislative candidates who advanced in the 2014 Election for the Regional House of Representatives of West Sumatra province. The study also looked at how the influence of cultural factors of matrilineal kinship system influenced the political process in the 2014 election. The research was conducted on 2 incumbent legislative candidates, and one candidate who advanced for the first time, but won the most votes among the six elected women. The research method is with qualitative case study, data obtained by in-depth interview with selected informant. The results reveal that the political strategy of women legislative candidates is an offensive strategy of market expansion and defensive strategy to preserve the market. Matrilineal kinship network also became one of the political strategies for women candidates. Keywords: political strategy, female legislative candidate, matrilineal kinship network ABSTRAK Paper ini fokus kepada pembahasan tentang bagaimana strategi politik perempuan calon legislatif yang maju dalam Pemilu 2014 untuk Dewan Perwakilan Rakyat Daerah provinsi Sumatera Barat. Penelitian ini juga melihat bagaimana pengaruh faktor budaya sistem kekerabatan matrilineal mempengaruhi proses politik dalam Pemilu 2014. Penelitian dilakukan terhadap 2 orang caleg petahana, dan satu orang caleg yang maju untuk pertamakali, tetapi berhasil meraih suara terbanyak diantara enam perempuan caleg terpilih. Metode penelitian adalah dengan kualitatif studi kasus, data diperoleh dengan wawancara mendalam dengan informan terpilih. Hasil penelitian mengungkapkan bahwa strategi politik perempuan caleg adalah strategi ofensif perluasan pasar dan strategi defensif memepertahankan pasar. Jaringan kekerabatan matrilineal juga menjadi salah satu strategi politik bagi perempuan caleg. Kata kunci: strategi politik, perempuan caleg, jaringan kekerabatan matrilineal